2020
DOI: 10.1200/jop.19.00747
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Oncology Care Model Reporting Requirements on Biomarker Testing and Treatment

Abstract: PURPOSE: The Oncology Care Model (OCM) is Medicare’s first alternative payment model program for patients with cancer. As of October 2017, participating practices were required to report biomarker testing of patients with advanced non–small-cell lung cancer (aNSCLC). Our objective was to evaluate the effect of this OCM reporting requirement on quality of care. METHODS: We selected patients with aNSCLC receiving care in practices in a nationwide de-identified electronic health record-derived database. We used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…First, respondents reported high biomarker testing rates that match or exceed levels observed by recent U.S.‐based studies, whose results vary significantly by year, practice setting, and biomarker. 7 , 9 , 12 Rates of guideline utilization (NCCN, ASCO, or other) among respondents, which correlated with high testing rates and use of multi‐gene panels, were high overall (98.8%) and equal among academic versus community respondents and generalist versus specialist respondents. Consistent testing for EGFR , ALK , and ROS1 for patients with non‐squamous NSCLC reported by 100% of respondents (98% for BRAF ) suggests familiarity with earlier approved treatments associated with those biomarkers regardless of practice setting, specialization, or other respondent characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, respondents reported high biomarker testing rates that match or exceed levels observed by recent U.S.‐based studies, whose results vary significantly by year, practice setting, and biomarker. 7 , 9 , 12 Rates of guideline utilization (NCCN, ASCO, or other) among respondents, which correlated with high testing rates and use of multi‐gene panels, were high overall (98.8%) and equal among academic versus community respondents and generalist versus specialist respondents. Consistent testing for EGFR , ALK , and ROS1 for patients with non‐squamous NSCLC reported by 100% of respondents (98% for BRAF ) suggests familiarity with earlier approved treatments associated with those biomarkers regardless of practice setting, specialization, or other respondent characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A 2020 analysis of 150 community oncology practices found that the percentage of patients receiving biomarker testing for EGFR, ALK, and/or ROS1 increased across practices from 2011 to 2018 (from about 55% to about 70%) but has since plateaued. 9 Rapid advancements in the diagnostic evaluation and treatment of NSCLC challenge oncologists to adapt their practices. Therefore, an American Society of Clinical Oncology (ASCO) taskforce comprised of representatives from community and academic oncology practices, the American Cancer Society (ACS) National Lung Cancer Roundtable (NLCRT), LUNGevity, the GO 2 Foundation for Lung Cancer, and the ROS1ders undertook this study to characterize U.S. oncologists' biomarker ordering practices, to determine the types of testing platforms used, and to ascertain the barriers to testing and subsequent impact of delays in testing on treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no significant difference, although testing rates and biomarker-guided therapy decisions increased over time in both groups. 38 Even with improved testing rates, opportunities still exist to improve test ordering and reporting processes. In our study, testing rates were higher according to unstructured data (cohort B) than structured data (Cohort A), indicating limitations in capture of data in structured fields.…”
Section: Discussionmentioning
confidence: 99%